Study on heterosis for yield and quality traits in rice (Oryza sativa L.) - Ramesh Babu, P; Sreelakshmi, Ch (ORYZA-An International Journal of Rice, 2020)
To know the extent of heterosis among the selected 21 crosses derived from the diallel mating system using seven parents regarding yield and quality traits. The magnitude of heterosis was high for grain yield and protein content and moderate to high for plant height, ear bearing tillers per plant, number of primaries per panicle, L/B ratio, head rice recovery and GT score. The best heterotic crosses for grain yield were erramallelux NLR 33637 and IR 72 x NLR 33637. The high heterotic effects in the hybrids may be due to predominant role of non additive component in the inheritance of the characters studied.